2009
DOI: 10.1073/pnas.0813280106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of all-trans retinoic acid/arsenic trioxide-based therapy in newly diagnosed acute promyelocytic leukemia

Abstract: All-trans retinoic acid (ATRA)/arsenic trioxide (ATO) combinationbased therapy has benefitted newly diagnosed acute promyelocytic leukemia (APL) in short-term studies, but the long-term efficacy and safety remained unclear. From April 2001, we have followed 85 patients administrated ATRA/ATO with a median follow-up of 70 months. Eighty patients (94.1%) entered complete remission (CR). Kaplan-Meier estimates of the 5-year event-free survival (EFS) and overall survival (OS) for all patients were 89.2% ؎ 3.4% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
332
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(356 citation statements)
references
References 42 publications
14
332
0
2
Order By: Relevance
“…According to data from the SIH, Kaplan --Meier estimates that the 5-year EFS and OS in a group of 85 newly diagnosed APL patients were 89.2% and 91.7%, respectively, demonstrating the high efficacy of ATRA/ATO treatment for newly diagnosed APL. 67 Recent literature supports our data in that the CR rate and EFS were relatively higher in the working groups using ATO/ATRA combination 68,69 compared with the groups using ATO alone. 59,60,62 GIMEMA group carried out a randomized phase III study to compare ATO þ ATRA versus standard ATRA þ anthracycline-based chemotherapy (AIDA regimen) for newly diagnosed non high-risk APL.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…According to data from the SIH, Kaplan --Meier estimates that the 5-year EFS and OS in a group of 85 newly diagnosed APL patients were 89.2% and 91.7%, respectively, demonstrating the high efficacy of ATRA/ATO treatment for newly diagnosed APL. 67 Recent literature supports our data in that the CR rate and EFS were relatively higher in the working groups using ATO/ATRA combination 68,69 compared with the groups using ATO alone. 59,60,62 GIMEMA group carried out a randomized phase III study to compare ATO þ ATRA versus standard ATRA þ anthracycline-based chemotherapy (AIDA regimen) for newly diagnosed non high-risk APL.…”
supporting
confidence: 87%
“…28,61 In the past two decades, the frequency of DS in our patients has been very low, 67 with the exception of a few patients presenting hyperleukocytosis at the diagnosis of the disease.…”
Section: Maintenance Therapymentioning
confidence: 75%
See 2 more Smart Citations
“…As ATO is used increasingly in APL patients and is a well known carcinogen, special attention should be paid to APL patients who received therapy with ATO. Hu et al recently reported that no secondary carcinoma was observed in 89 APL patients received ATRA and ATO combinational therapy with a median follow-up of 70 months [13]. However, there was initially observed an increased risk of second solid tumors subsequent to ATO treatment for APL [14], and there was a reported case that t-AML developed after APL receiving chemotherapy and arsenic agent as maintenance treatment [15].…”
Section: Discussionmentioning
confidence: 99%